FACTORS INFLUENCING USER SATISFACTION AND CONTINUANCE INTENTION IN MOBILE PAYMENT APPS IN CAMBODIA: A STRUCTURED LITERATURE REVIEW - Vannak, Kun; Hong, Dr. Soun; Rady, Dr. Chhun (Srawung: Journal of Social Sciences and Humanities, 2025)
Even tough mobile payment has been increasing adopted in Cambodia, there is a lack of business and academic study on the building of the conceptual model. This academic article systematically reviews factors influencing user satisfaction and continuance intention for mobile payment applications in Cambodia. It integrates the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), along with other constructs like perceived service quality, credibility, compatibility, and perceived risk. The research emphasizes user satisfaction as a crucial mediator for sustained engagement, noting Cambodia's rapid adoption of mobile payments due to government initiatives. The study concludes by proposing a conceptual model and outlining research methodology involving document analysis and thematic synthesis of scholarly papers, all factors have a significant impact on user satisfaction and continuance intention to adopt mobile payment; however, perceived risk has a negative impact on both user satisfaction and continuance intention. These findings open floor for future study by using a certain sophisticated statistical tool.